Geriatric Femoral Neck Fractures: Hemiarthroplasty Implant Trends Across a Health System From 2006 to 2018. (9th June 2020) - Kibble, Kendra; Peck, Sarah C.; Parikh, Harsh R.; Flagstad, Ilexa; Gorman, Tiffany; Okelana, A. Bandele; Cunningham, Brian P.
Introduction: Hemiarthroplasty is increasingly used for the treatment of geriatric femoral neck fractures in an effort to optimize value-based care. The current American Association of Orthopaedic Surgeons (AAOS) guidelines released in 2014 for the treatment of geriatric hip fractures recommend the utilization of monopolar cemented constructs. The purpose of this study was to evaluate hip hemiarthroplasty implant cost variability and implant selection trends from 2006 to 2018. Materials and Methods: A retrospective review of 940 geriatric hip fractures treated with hemiarthroplasty was conducted across 3 institutions from 2006 to 2018. Variables examined were construct type, surgeon, operative time, patient mortality, and implant cost. Statistical analysis consisted of multigroup comparative tests and multiple linear regression analyses to evaluate correlative measures. Results: The study population was 85.0 ± 7.9 years of age with a body mass index of 24.0 ± 5.5. A total of 33 (3.5%) patients were deceased at the 90-day postoperative mark and 45 (4.8%) patients at the 1-year mark. There was no statistical difference in terms of mortality between the 4 implant cohorts at the 90-day mark ( P = .56) and 1-year mark ( P = .24). The bipolar press-fit construct was the most expensive, US$3900.61 ± US$2607.54, and the monopolar cemented construct was the least expensive, US$2618.68 ± US$1834.16. The mean operative time was 6 minutes greater for press-fit implants, 93.6 ± 32.0, than cemented implants, 87.1 ± 33.6 ( P = .02). The use of monopolar cemented implants increased from 12.1% to 83.3%, while bipolar press-fit decreased from 57.6% to 4.6% from 2013 to 2018. Discussion: The use of a bipolar and/or press-fit implant significantly increases construct cost despite little evidence in the literature of improved outcomes. Contrary to previous research, cemented implants do not increase the operative time. Conclusions: Encouragingly, selection of the most cost-conscience implant, monopolar cemented, has been increasing since 2014, which may reflect the influence of current AAOS guidelines. Level of Evidence: Diagnostic Level III.